MARKETING AWARENESS OF CROSSBORDER DESTINATION - THE CASE STUDY OF BIHOR- HAJDU/BIHAR EUROREGION - Corina-Florina TĂTAR; Tomasz STUDZIENIECKI; Klara CZIMRE; Janos PENZES (Geo Journal of Tourism and Geosites, 2020)
The study aims to highlight the high education students’ awareness about the tourism opportunities of the Bihor-Hajdu-Bihar euroregion of north-western Romania and eastern Hungary respectively, through a survey applied to the students of the University of Oradea and Debrecen cities, as county seats of the of Bihor and Hajdu-Bihar. The respondents’ answers were stored into an SPSS database and its results processed and analyzed through generated charts. The results showed that most respondents claim for a better marketing of the euroregion and its activities, through internet and websites, indicating an eagerness to find out more about its potentialities. Most respondents were aware of the tourist attractions that the county from their side of the border offers, but only five respondents could provide tourist attractions that belong to the other side of the border, thus indicating that the euroregion is not yet perceived as a single tourist destination on the market. Therefore 79,7% of the respondents could name correctly one tourist attraction that belongs to the euroregion, more than half (67,2%) could provide two attractions and less than a half (40,6%) could provide three tourist attractions as incentives for visitation and marketing.